Molecular Composition of Dissolved Organic Matter in Sediment Porewater of the Arctic Deep-Sea Observatory HAUSGARTEN (Fram Strait) - Rossel, Pamela E.; Bienhold, Christina; Hehemann, Laura; Dittmar, Thorsten; Boetius, Antje (Frontiers in Marine Science, 2020)
Over the last decades, the Arctic Ocean has suffered a substantial decline in sea-ice cover due to global warming. The impacts of these variations on primary productivity, fluxes of dissolved and particulate organic matter (OM) and turnover at the seafloor are still poorly understood. Here we focus on the characteristics and dynamics of the pool of marine dissolved OM (DOM) in surface sediments of the Arctic Ocean. To investigate spatial and temporal variations of DOM in relation to particulate OM input and benthic microbial community parameters, sediment porewater and overlying bottom water were collected from the long-term observatory HAUSGARTEN in June 2013 and 2014. The study area in the Fram Strait, which is partially covered by sea ice, was sampled along a bathymetric transect (1050-5500 m water depth), from east to west (7°0.2' E to 5°17' W), and from south to north (78°37' to 79°43' N). Molecular data on solid phase extracted DOM obtained via Fourier Transform Ion Cyclotron Resonance Mass Spectrometric analysis and a suite of bulk chemical parameters were related to benthic biogeochemical data. Our results demonstrate a close coupling between the production and input of OM from the surface ocean to the seafloor, and the concentration and composition of DOC/DOM in the deep sea. Surface porewaters collected in 2013 from shallower stations (≤ 1500 m water depth) in the eastern Fram Strait, had a signal of a larger and more recent input of OM (higher concentrations of phytodetritus), associated with higher numbers of molecular formulas, higher abundances of unsaturated aliphatic formulas and N-containing compounds, in concert with higher enzymatic activity, phospholipids, total organic carbon and protein content. In contrast, porewaters collected in 2014 from deeper stations and from the West, were associated with lower OM input, and showed higher abundances of aromatic and oxygen-poor compounds. Higher OM input was also reflected in higher DOC concentrations and fluxes from the sediment into the water column. Our study demonstrates that regional and temporal variations in OM input can quickly translate into changes in the quantity and quality of surface porewater DOM, the latter substantially altered by deep-sea sediment bacteria.